al-‘Alaqah Bayna Kafaah Nuthq al-Huruf al-‘Arabiyah wa Qudroh al-Thullab fi al-Imla’ - Zimatullah, Yani; Rozaanah, Rozaanah; Tumanggor, Ilham (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
The purpose of this study was to determine the correlation between ability to pronounce Arabic letters and Imla' ablity in first grade students of SMP Ma'had Tahfizul Qur'an Fajar Islam Tanjung Morawa. The method used is a quantitative approach with a correlation method and the data analysis method uses statistical data with the Product Moment formula to find the results of the study. The result is that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. That is, there is a correlation between ability to pronounce Arabic letters and Imla’ ability in first grade students of SMP Ma'had Tahfizul Qur'an Fajar Islam Tanjung Morawa with a correlation value of 0.765 which shows a strong and unidirectional correlation.